SPECIFIC FEATURES OF TEACHING HISTORY AS AN ACADEMIC SUBJECT (Eureka Journal of Education & Learning Technologies, 2026)
Teaching history plays a crucial role in shaping learners’ worldview, critical thinking, and national identity. Unlike many other academic disciplines, history focuses on past events, social processes, and human experiences, requiring specific pedagogical approaches. This article analyzes the distinctive features of teaching history, including its educational, developmental, and value-oriented functions. Special attention is given to historical thinking, source-based learning, interdisciplinarity, and the use of modern teaching methods. The study highlights the importance of history education in fostering civic responsibility and analytical skills among students.
Keywords: History education, teaching methods, historical thinking, interdisciplinarity, critical analysis.